ANALISIS PENGARUH SUPPLY CHAIN MANAGEMENT TERHADAP KINERJA PERUSAHAAN (Studi Pada Industri Kecil dan Menengah Makanan Olahan Khas Padang Sumatera Barat) - Ariani, Desi; Munas Dwiyanto, Bambang (Diponegoro Journal of Management, 2013)
Small and medium industry have important role in developing manufacture industries in West Sumatra especially in food sector. Food processing industry in Padang, is potential industry to be developed. Product competitiveness is still lacking in small and medium food processing industry in Padang. The product distribution is still difficult, this matter need to be considered for the company through the increasing performance. The purpose of this research is to analyze the influence of supply chain management toward company performance. The population in this research is small and medium industry in Padang city that operating in food processing in Padang. The sample that used is 100 small and medium industry from the entire population of 736 small and medium industry, that taken by simple random sampling and the collected data is using questionnaire. Technique analysis used is multiple linear regression that operated by SPSS programe. Variable information sharing, long term relationship, cooperation and process integration have positive and significant influence toward supply chain management performance on company. Process integration has the biggest significant value, and then information sharing then long term relationship and cooperation. All hypothesis was accepted because the significant value is lower than 0,05. The result of coefficient determinant is 0,318, it shows that the ability of independent variable in explaining dependent variable is 31,8%.